Portugal : Financial Sector Assessment Program; Detailed Assessment of Observance of IAIS Insurance Core Principles. (IMF Staff Country Reports; Country Report ;, 2007)
This Detailed Assessment of the Observance of International Association of Insurance Supervisors (IAIS) Insurance Core Principles for Portugal highlights the market analysis of the insurance market. Investment in domestic government bonds has decreased and is outweighed by nondomestic government bonds. The structure of own funds has been subject to the revaluation reserve that incorporates the changes in the market value of investments. Instituto de Seguros de Portugal (ISP) appreciated the appraisal of efforts undertaken to strengthen insurance supervision on the basis of a forward-looking and risk-based approach.